Assessment of Diabetes Knowledge Among The Government Employees of Tamil Nadu - Ramkumar, N. R; Mohanakrishnan, R.; Veeran, V. (Journal of Neonatal Surgery, 2025)
The active management of type 2 diabetes, a metabolic disorder, entails not only the use of supplements but also patient awareness of the need to make significant lifestyle changes. It's expected that those who understand hypoglycemia better would continue to control their blood sugar amounts. Diabetes awareness among Tamil Nadu government employees was assessed using the Diabetes awareness Questionnaire (DKQ). A cross-sectional research of Tamil Nadu government workers was carried out. Both sexes of subjects who were able to comprehend and finish interviews and were between the ages of 32 and 60 were recruited. Subjects who were unable of comprehending and filling out the forms and who were unwilling to participate were excluded. The investigation found that the population's understanding of diabetes was mediocre. A healthy diet and adequate exercise were not being followed by the majority of people. About 40% of parents in the population have diabetes. It may be possible to improve glycaemic management by increasing the understanding of diabetics. If a clinical pharmacist is involved with vigorous exercise and eating properly, this goal of increasing people's understanding of diabetes may be accomplished over time.